Closed-Loop Knowledge Risk Management in IT Company - Ardijan Handijono; Zaldy Suhatman (Jurnal Informatika Universitas Pamulang, 2021)
Today, organizations are surrounded by a volatile environment, which may change at any time and can be a new risk. Therefore, organizations must arm themselves with comprehensive knowledge to be able to deal with the risks posed by an unstable environment. In order for organizations to obtain comprehensive risk information, Knowledge Risk Management (KRM) is needed, which is the intersection of two previously separate fields, namely Risk Management (RM) and Knowledge Management (KM). How can KM reduce risk leading to better risk management? how can the KM process increase RM? and what is the mutually reinforcing integration between RM and KM? To address these questions, the researcher conducted a systematic literature review (SLR) of 42 relevant empirical studies. In order to improve the efficiency of the RM process using the KM process, a knowledge-based risk management (KBRM) process will be used. Utilization of KRM can significantly support the achievement and maintenance of competitive advantage and bring several benefits to software development.